Standarisasi Mutu Ekstrak Etanol Bunga Soka (Ixora coccinea L.) - Cut Yuliana; Ria Ceriana; Rini Shafriyani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Standardization is the process of determining properties based on certain parameters to achieve the same degree of quality. The extract was standardized with two parameters, namely specific and non-specific parameters. So that the efficacy and quality of this soka flower extract can be guaranteed, it is necessary to meet a quality standard for the product/extract material by standardizing the extract. Standardization is carried out so that uniform raw materials can be obtained which can finally guarantee the pharmacological effects of these plants. Standardization is the process of guaranteeing the final product (simplicia, extract or herbal product) to have certain parameter values ​​that are constant and predetermined. The research method is by testing various parameters on the extract, starting with determining the species of soka flower, then calculating the yield, organoleptic testing, water content, water soluble compounds, ethanol soluble compounds. The average water content test result is 9.54% and is still within the permissible standard, the water content in medicinal preparations including extracts should not exceed the 10% limit. Based on the results of determination of water soluble extract content of 20.7% and ethanol soluble extract content of 35.5%. The ethanol soluble extract content was higher than the water soluble compounds, thus the semi-polar compounds in the extract were higher than the polar compounds